2002
DOI: 10.1055/s-2002-20165
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Intramural Coronary Arteries after Arterial Switch Operation

Abstract: The intramural course of coronary arteries in patients with d-TGA is rare and does not cause increased mortality or myocardial infarction rates. However, the risk of coronary occlusion over time seems to be high. Therefore, patients with this condition require selective coronary angiography and frequent exercise investigations. Revascularization with an internal mammary artery bypass may be indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Vessel reimplantation has been described [57], but Rinaldi et al [45] reported their poor results with reimplantation, as two patients required emergency bypass grafting. In an analogous procedure, reimplantation of intramural coronaries during arterial switch for transposition of the great arteries is also associated with high occlusion rates [58]. The most promising procedure involves bunroofingQ the anomalous vessel from its intramural course, allowing modification of the slit-like ostium of the anomalous coronary, which becomes fully patent after reconstruction.…”
Section: Surgical Managementmentioning
confidence: 99%
“…Vessel reimplantation has been described [57], but Rinaldi et al [45] reported their poor results with reimplantation, as two patients required emergency bypass grafting. In an analogous procedure, reimplantation of intramural coronaries during arterial switch for transposition of the great arteries is also associated with high occlusion rates [58]. The most promising procedure involves bunroofingQ the anomalous vessel from its intramural course, allowing modification of the slit-like ostium of the anomalous coronary, which becomes fully patent after reconstruction.…”
Section: Surgical Managementmentioning
confidence: 99%
“…2,10 Corrective surgery is recommended for intramural segment cases. 3,11 An unroofing procedure is typically performed to correct the intramural segment. 2,3 Several repair procedures may be utilized depending on the nature of the patient's abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the actuarial freedom from a coronary event of these patients for ten years would be 46%. Sachweh et al [11] reported that they found an intramural coronary artery in 5 patients (1.4%) of 351 who underwent ASO, and they transferred the intramural coronary artery as one button without unroofing the aortic wall. They also reported that, though there were neither operative mortality nor myocardiac ischemia, intramural coronary artery obstructions were identified by coronary angiograms that were performed at postoperative 5, 16, and 53 months later, and 2 of the patients had operations for a coronary artery bypass graft using an internal mammary artery.…”
Section: Discussionmentioning
confidence: 99%